Super-hydrophobic coating and preparation method thereof

By constructing nanostructures on the surface of millimeter-level sand and gravel particles, forming milli-nano structured sand and gravel particles, and fusing them with resin adhesives, the problem of unstable flexibility and impact resistance of superhydrophobic coatings is solved, and the preparation of high-performance superhydrophobic coatings is achieved.

CN119684827APending Publication Date: 2025-03-25周继贵
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411992128.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

While ensuring superhydrophobic properties, the existing superhydrophobic coatings have unstable flexibility and impact resistance, which are prone to "powder loss", resulting in a significant reduction in superhydrophobic properties.

Method used

The superhydrophobic coating is prepared by constructing nanostructures on the surface of millimeter-scale sand and gravel particles, forming milli-nano structure sand and gravel particles, and fusing them with resin adhesive to form a film.

Benefits of technology

This method not only maintains the superhydrophobic properties of the coating, but also significantly improves its flexibility and impact resistance, ensuring the mechanical stability and durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684827A_ABST
    Figure CN119684827A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophobic coating and a preparation method thereof, and belongs to the technical field of super-hydrophobic coatings. The preparation method of the super-hydrophobic coating comprises the following steps: providing gravel particles with the diameter of millimeter level; carrying out acid etching treatment on the sandstone particles to obtain etched sandstone particles; the etched gravel particles are subjected to surface modification treatment, and the gravel particles of the nano-nano structure are obtained; coating an adhesive on the surface of a base material to obtain an adhesive film; and uniformly coating the gravel particles with the nano-nano structure on the surface of the adhesive film, and carrying out curing treatment to obtain the super-hydrophobic coating. The coating provided by the invention has good super-hydrophobic performance and also has good mechanical properties such as flexibility, impact resistance and the like. As a strong chemical interaction force exists between the nano structure on the surface of the gravel particle with the nano-nano structure and the whole particle, the nano structure and the whole particle are tightly connected and are not easy to separate, the stability and durability of the structure are ensured, and the stability of the super-hydrophobic performance of the coating is further ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of super hydrophobic coatings, and in particular to a super hydrophobic coating and a preparation method thereof. Background Art

[0002] Super-hydrophobic coatings have broad application prospects in architectural coatings. Their unique waterproof, self-cleaning and anti-corrosion properties can effectively protect the exterior walls, roofs and glass surfaces of buildings, improve weather resistance and aesthetics, and reduce maintenance costs. With the continuous advancement of technology, the performance of super-hydrophobic coatings will be even better, and their application areas will continue to expand. In the future, super-hydrophobic coatings will become an important development direction for the architectural coatings industry, contributing to green buildings and energy conservation and environmental protection.

[0003] In view of the unique effectiveness and importance of super-hydrophobic coatings, many scholars have conducted extensive and in-depth research on them in the past few decades. Studies have shown that constructing a "concave-convex micro-nano" structure on the coating surface is the core of giving the coating super-hydrophobic properties. At present, there are various methods for constructing super-hydrophobic coatings, mainly including chemical methods and physical methods. Chemical methods such as solution impregnation, deposition and chemical modification methods achieve super-hydrophobicity by changing the chemical composition and structure of the coating surface. Physical laws include template methods, solvent evaporation methods and polymer / nanomaterial blending methods, which achieve the purpose by changing the physical structure of the coating surface. Among them, the polymer / nanomaterial blending method has significant advantages. Not only is the preparation method simple, but it can also achieve continuous mechanized construction and improve coating efficiency, and has broad application prospects.

[0004] However, in the preparation process of polymer / nano material blending method, in order to give the coating unique super-hydrophobic properties, it is often necessary to add a large amount of nano materials, which brings a series of challenges. Because the pigment-to-base ratio (ratio of pigment to base material) of the coating is much higher than the critical value, the mechanical properties of the coating are affected, especially the flexibility and impact resistance are unstable. In practical applications, this unstable mechanical property often causes the coating surface to appear "powdering" phenomenon, that is, the nano-pigment particles in the coating fall off due to bending and impact by external force. Once the coating appears "powdering", its super-hydrophobic performance will be greatly reduced or even completely lost. Therefore, how to improve the flexibility and impact resistance of the coating while ensuring super-hydrophobic performance is one of the problems to be solved in the current super-hydrophobic coating research. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a super-hydrophobic coating and a preparation method thereof, aiming to solve the problem that the flexibility and impact resistance of the coating are unstable while ensuring the super-hydrophobic properties of the coating.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a method for preparing a super-hydrophobic coating, comprising:

[0008] Step A, providing sand and gravel particles with a diameter of millimeters;

[0009] Step B, subjecting the sand and gravel particles to acid etching to obtain etched sand and gravel particles;

[0010] Step C, performing surface modification treatment on the etched sand and gravel particles to obtain milli-nano structured sand and gravel particles;

[0011] Step D, applying the adhesive to the surface of the substrate to obtain an adhesive film;

[0012] Step E: evenly coating the milli-nano structured sand and gravel particles on the surface of the film, and subjecting the coating to curing treatment to obtain a super hydrophobic coating.

[0013] Optionally, the step B specifically includes:

[0014] The sand and gravel particles are cleaned and then spread out to air dry;

[0015] The air-dried sand and gravel particles are placed in an acid etching solution, and after being acid-etched for a predetermined time, they are dried to obtain etched sand and gravel particles.

[0016] Optionally, the acid etching solution includes H2O, HF and HCl, and the volume ratio of H2O, HF and HCl is 30:4.5 to 10:1.

[0017] Optionally, the predetermined time is 8 to 12 hours.

[0018] Optionally, the step C specifically comprises: placing the etched sandstone particles in a 1H, 1H, 2H, 2H-heptadecafluorodecyl trichlorosilane solution to perform surface modification treatment to obtain milli-nanostructured sandstone particles;

[0019] The 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane solution is prepared from 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane and an organic solvent, and the organic solvent includes at least one of n-hexane, ethanol and dichloromethane.

[0020] Optionally, the surface modification treatment time is 10 to 12 hours.

[0021] Optionally, the mass ratio of the volume of the organic solvent to 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane is 30mL:0.5-1g.

[0022] Optionally, in step D, the adhesive is epoxy resin, silicone resin, acrylic resin or a two-component adhesive, and the thickness of the adhesive film is 1 to 3 mm.

[0023] Optionally, in step E, the curing time is 18 to 36 hours.

[0024] A second aspect of the present invention provides a super hydrophobic coating, wherein the super hydrophobic coating is prepared by the method for preparing the super hydrophobic coating of the present invention;

[0025] And / or, the super-hydrophobic coating includes a film and milli-nano structured gravel particles uniformly distributed on the surface of the film, and the milli-nano structured gravel particles include gravel particles with a diameter of millimeters and nanostructures combined on the surface of the gravel particles.

[0026] Beneficial effects: The present invention constructs nanostructures on the surface of millimeter-level sand and gravel particles to form milli-nanostructured sand and gravel particles, and then fuses them with resin adhesives to form a film. The obtained coating has good super-hydrophobic properties and also has good mechanical properties such as flexibility and impact resistance. Because there is a strong chemical interaction force between the nanostructure on the surface of the milli-nanostructured sand and gravel particles and the overall particles, they are closely connected to each other and difficult to separate, thereby ensuring the mechanical stability and durability of the structure, and then ensuring the stability of the super-hydrophobic properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure is a schematic flow chart of a method for preparing a super-hydrophobic coating in a specific embodiment of the present invention.

[0028] Figure 2 These are the surface microscopic morphology images of milli-nanostructured sand and gravel particles in the specific embodiments of the present invention, wherein (a) is the surface microscopic morphology enlarged 500 times, (b) is the surface microscopic morphology enlarged 2000 times, (c) is the surface microscopic morphology enlarged 5000 times; and (d) is the surface microscopic morphology enlarged 20000 times.

[0029] Figure 3 This is a graph showing the surface chemical composition characterization results of milli-nanostructured sand and gravel particles in a specific embodiment of the present invention.

[0030] Figure 4 This is a characterization result diagram of the surface chemical element distribution content of milli-nano structured sand and gravel particles in a specific embodiment of the present invention.

[0031] Figure 5 Graphs showing the hydrophobic properties of coatings in specific embodiments of the present invention, wherein (a) is a water contact angle of 155.1°, (b) is a water contact angle of 152.9°, (c) is a water contact angle of 155.8°, and (d) is a water droplet rolling angle of 3.8°.

[0032] Figure 6 Graph showing the flexibility of the coating in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0033] The present invention provides a super hydrophobic coating and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0034] At present, in the preparation process of super-hydrophobic coating, in order to give it unique super-hydrophobic properties, it is often necessary to add a large amount of nano materials. However, this approach also brings a series of challenges. Because the pigment-to-base ratio (ratio of pigment to base material) of the coating is much higher than the critical value, the mechanical properties of the coating are affected, especially the flexibility and impact resistance become unstable. In practical applications, this unstable mechanical property often leads to the "powdering" phenomenon on the surface of the coating, that is, the nano-pigment particles in the coating fall off due to bending or impact by external force. Once the coating "powdering" occurs, its super-hydrophobic performance will be greatly reduced or even completely lost. Therefore, how to improve the mechanical stability of the coating while ensuring super-hydrophobic performance is one of the problems to be solved in the current research on super-hydrophobic coatings.

[0035] Research has found that even with extremely low resin content, building exterior wall mortar paint can form a strong and continuous coating through the mutual bonding of millimeter-sized sand and gravel particles, and fit tightly to the wall. This excellent bonding strength is due to the large size and low specific surface area of ​​millimeter-sized sand and gravel particles, which enables good bonding between particles and between particles and substrates at high pigment volume concentrations to form a hard whole.

[0036] Inspired by this, it is conceivable that if nanostructures are constructed on the surface of millimeter-sized particles to form milli-nanostructured sand and gravel particles, and then they are fused with resin to form a film, it may be possible to give the coating super-hydrophobic properties while greatly improving its mechanical stability. Because there is a strong chemical interaction between the nanostructure on the surface of the milli-nanostructured sand and gravel particles and the overall particles, they are closely connected to each other and difficult to separate, thus ensuring the stability and durability of the structure, providing a unique advantage for building high-performance super-hydrophobic coatings.

[0037] Based on this, the present invention selects millimeter-sized sand and gravel particles, uses acid etching technology, and carefully constructs nanoscale structure on the surface of millimeter-sized sand and gravel particles. Subsequently, the surface is further optimized by chemical modification (the purpose is to reduce the particle surface energy, to promote its hydrophobicity), and the second-order milli-nano structure sand and gravel particles with low surface energy characteristics are successfully prepared. The particle not only retains the original firmness of the sand and gravel particles, but also gives it super-hydrophobicity at the microscopic level. The second-order milli-nano structure sand and gravel particles are mixed with high-performance adhesives, and a super-hydrophobic coating with excellent physical and mechanical properties is successfully obtained. The coating not only has outstanding super-hydrophobicity, but also performs well in aspects such as anti-bending and impact resistance, and provides solutions for application scenarios such as building exterior walls.

[0038] Specifically, an embodiment of the present invention provides a method for preparing a super-hydrophobic coating, which comprises:

[0039] Step A, providing sand and gravel particles with a diameter of millimeters;

[0040] Step B, subjecting the sand and gravel particles to acid etching to obtain etched sand and gravel particles;

[0041] Step C, performing surface modification treatment on the etched sand and gravel particles to obtain milli-nano structured sand and gravel particles;

[0042] Step D, applying the adhesive to the surface of the substrate to obtain an adhesive film;

[0043] Step E: evenly coating the milli-nano structured sand and gravel particles on the surface of the film, and subjecting the coating to curing treatment to obtain a super hydrophobic coating.

[0044] The embodiment of the present invention selects millimeter-sized sand and gravel particles, and uses acid etching technology to construct nanoscale structures on the surface of millimeter-sized sand and gravel particles. Subsequently, the surface is modified by a chemical modification method to obtain second-order milli-nanostructure sand and gravel particles with low surface energy characteristics. The surface of the particle has a large number of uneven nanostructures with gaps, and the nanostructure is a white granular substance. This structure not only retains the original firmness of the sand and gravel particles, but also gives them super-hydrophobic properties at the microscopic level.

[0045] The second-order milli-nanostructured gravel particles are mixed with a high-performance adhesive to form a film, and a super-hydrophobic coating with good mechanical properties is obtained. The coating not only has good super-hydrophobic properties, but also has excellent flexibility and impact resistance, thereby ensuring the stability of the super-hydrophobic properties of the coating. This is due to the large overall size of the gravel particles. Under the action of the resin, there is a better bonding effect between the particles and between the particles and the substrate, and it is not easy to be destroyed and separated from each other, and has good structural stability. Therefore, when impacted by the outside world, a good microscopic rough structure can still be maintained, so that its surface still has excellent super-hydrophobic properties.

[0046] In one embodiment, in step A, the diameter of the sand and gravel particles is 1 to 3 mm.

[0047] In one embodiment, the step B specifically comprises:

[0048] The sand and gravel particles are cleaned and then spread out to air dry;

[0049] The air-dried sand and gravel particles are placed in an acid etching solution, and after being acid-etched for a predetermined time, they are dried to obtain etched sand and gravel particles.

[0050] In one embodiment, the acid etching solution includes H2O, HF and HCl, and the volume ratio of H2O, HF and HCl is 30:4.5 to 10:1.

[0051] In one embodiment, the predetermined time is 8 to 12 hours, such as 8 hours, 10 hours, 12 hours, etc.

[0052] In one embodiment, the drying temperature is 70-90° C. (such as 80° C.), and the drying time is 20-40 min (such as 30 min).

[0053] In one embodiment, the step C specifically comprises: placing the etched sandstone particles in 1H, 1H, 2H, 2H,-heptadecafluorodecyl trichlorosilane ( The surface of the sandstone particles was modified by FDTS solution to obtain milli-nano structure sandstone particles.

[0054] The 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane solution is prepared from 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane and an organic solvent, and the organic solvent includes at least one of n-hexane, ethanol and dichloromethane.

[0055] After FDTS is hydrolyzed (the solvent and air contain a small amount of water), it reacts with the hydroxyl groups on the surface of the sand and gravel particles and adheres to their surface. However, the density of hydroxyl groups on the surface of the particles is limited, so some FDTS self-assembles during the modification process, resulting in the agglomeration of FDTS, and then forms nano-scale white granular substances on the surface of the sand and gravel particles, obtaining milli-nanostructured sand and gravel particles.

[0056] In one embodiment, the surface modification treatment time is 10 to 12 hours.

[0057] In one embodiment, the mass ratio of the volume of the organic solvent to 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane is 30mL:0.5-1g.

[0058] In one embodiment, in step D, the thickness of the adhesive film is 1 to 3 mm, such as 2 mm.

[0059] In one embodiment, the adhesive may be epoxy resin, silicone resin, acrylic resin or a two-component adhesive.

[0060] In one embodiment, the substrate is tinplate, but is not limited thereto, and the tinplate is polished tinplate.

[0061] In one embodiment, in the step E, the curing time is 18 to 36 hours, such as 24 hours.

[0062] An embodiment of the present invention provides a super-hydrophobic coating, wherein the super-hydrophobic coating is prepared by the method for preparing the super-hydrophobic coating described in the embodiment of the present invention;

[0063] And / or, the super-hydrophobic coating includes a film and milli-nanostructured gravel particles uniformly coated on the surface of the film, and the milli-nanostructured gravel particles include gravel particles with a diameter of millimeters and nanostructures combined on the surface of the gravel particles.

[0064] The embodiment of the present invention constructs a nanostructure on the surface of millimeter-level sand and gravel particles to form milli-nanostructured sand and gravel particles, which are then fused with resin to form a film. The obtained coating has good super-hydrophobic properties and good mechanical properties. Because there is a strong chemical interaction force between the nanostructure on the surface of the milli-nanostructured sand and gravel particles and the overall particles, they are closely connected to each other and difficult to separate, thereby ensuring the stability and durability of the structure, and then ensuring the stability of the super-hydrophobic properties of the coating.

[0065] The present invention is described in detail below through specific embodiments.

[0066] Combination Figure 1 As shown, the present embodiment provides a method for preparing a super hydrophobic coating, comprising the following steps:

[0067] 1. Construction of milli-nanostructured sand and gravel particles

[0068] (1) Take 120g of sand and gravel particles with a diameter of 1 to 3mm, clean them, and spread them flat to air dry.

[0069] (2) Take 4.5 g of dry sand and gravel particles and spread them evenly (not too thick) in a container.

[0070] (3) Weigh 60 mL of H2O, 12 mL of HF, and 2 mL of HCl in a volume ratio of 30:6:1 and add them into the container, and etch for 8 h.

[0071] (4) Make sure to shake well and keep the timing.

[0072] (5) After etching, clean and dry at 80℃ for 30min.

[0073] (6) After drying, 30 mL of n-hexane and 0.5 g of 1H,1H,2H,2H,-heptadecafluorodecyltrichlorosilane were added into the container and the modification was carried out for 10 h.

[0074] (7) After modification, the particles are taken out and dried to obtain milli-nano structured gravel particles.

[0075] 2. Preparation of super-hydrophobic coating

[0076] The adhesive epoxy resin is applied to the polished tinplate surface to form a 2 mm thick film; the milli-nanostructured sand and gravel particles are evenly coated on the film surface and cured for 24 hours to obtain a super-hydrophobic coating.

[0077] 3. Characterization of coating performance

[0078] 3.1 Surface morphology and chemical composition of particles

[0079] The microstructure and surface elemental composition of the particles were characterized and analyzed using a field emission scanning electron microscope (ZEISS Sigma300SEM, Germany) equipped with a Smartedx energy spectrometer (EDS). During the test, the sample was imaged using a SE2 secondary electron detector at an accelerating voltage of 3 kV. The EDS spectrum was tested under the conditions of an accelerating voltage of 15 kV and a working distance of 8.5 mm. At the same time, an X-ray photoelectron spectrometer (XPS) equipped with a monochromatic Al Kα source (hν=1486.6 eV) was used to analyze the chemical composition of the particle surface at room temperature. During the test, the power was 12 kV×6 mA and the spot size was 400 μm.

[0080] 3.2 Coating properties

[0081] Superhydrophobicity: The water contact angle of the coating was characterized using an optical water contact angle tester (Lauda Scientific LSA100, Germany). The final static water contact angle was represented by the average value of the test results of different areas of the coating.

[0082] Flexibility: According to GB / T1731-2020 "Determination of paint film flexibility", a paint film flexibility tester (BGD560, China) is used to evaluate the bending resistance of the coating. With the coating surface facing up, use both hands to press the coating sample tightly onto a shaft rod of the specified diameter of the flexibility tester, bend the test plate around the shaft rod at a steady speed within 2 to 3 seconds, and observe whether the coating has reticulation, cracks, and peeling.

[0083] 4. Characterization results

[0084] Figure 2The surface microstructure of milli-nanostructured sand and gravel particles is shown. Figure 2 It can be seen that a large number of uneven nanostructures with gaps appear on the surface of the modified milli-nanostructured sandstone particles. These structures have low surface energy and strong air adsorption capacity, which is conducive to the formation of a stable air layer, thereby achieving super hydrophobic properties of the coating. EDS analysis was performed on them ( Figure 3 ) found that the five elements F, Si, Cl, C, and O were evenly distributed on the particle surface, and their mass fractions on the particle surface were 57.52%, 0.76%, 1.75%, 27.84%, and 12.14%, respectively. Figure 4 ). This is because FDTS reacts with the hydroxyl groups on the particle surface after hydrolysis and adheres to the particle surface. However, the density of hydroxyl groups on the particle surface is limited, so some FDTS self-assembles during the modification process, resulting in the agglomeration of FDTS, and then forms white granular substances on the particle surface.

[0085] Depend on Figure 5 As can be seen from (a) to (c), the water droplets are distributed in a spherical shape on the coating surface. The water contact angles in three different areas are 155.1°, 152.9°, and 155.8°, respectively, with an average of 154.6°, which is higher than the critical value of 150°, achieving super hydrophobic properties. In addition, the rolling angle of the coating was also tested (see Figure 5 In (d), the contact angle reaches 3.8°, which indicates that the water droplets can hardly wet the coating surface, but form an almost perfect sphere. This extremely high water contact angle means that the coating has excellent superhydrophobic properties and can effectively resist external moisture, such as rain, dew, etc. The above results show that a superhydrophobic coating with stable performance was prepared using milli-nanostructured sand and gravel particles as functional pigments.

[0086] The coating is placed on a 2mm diameter shaft and bent 180° around the shaft. There is no crack or peeling in the bent section of the coating. Figure 6 As shown, the flexibility reaches 2mm. When a water drop is dropped on the curved section, the drop is deformed by the impact and then rebounds and falls. There is no adsorption residue on the surface, indicating that the curved surface of the coating has good impact resistance and excellent hydrophobic properties.

[0087] In summary, a kind of super-hydrophobic coating and preparation method thereof provided by the present invention, the present invention forms milli-nano structure sand and gravel particles by constructing nanostructure on the surface of millimeter-level sand and gravel particles, and then fuses it with resin into film, and the coating obtained has excellent super-hydrophobic performance, and also has good mechanical stability performance. Because there is a strong chemical interaction force between the nanostructure on the surface of this milli-nano structure sand and gravel particles and the overall particles, they are closely connected to each other and are not easy to separate, so as to ensure the stability and durability of the structure, and then ensure the stability of the super-hydrophobic performance of the coating.

[0088] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a super hydrophobic coating, characterized in that, include: Step A, providing sand and gravel particles with a diameter of millimeters; Step B, subjecting the sand and gravel particles to acid etching to obtain etched sand and gravel particles; Step C, performing surface modification treatment on the etched sand and gravel particles to obtain milli-nano structured sand and gravel particles; Step D, applying the adhesive to the surface of the substrate to obtain an adhesive film; Step E: evenly coating the milli-nano structured sand and gravel particles on the surface of the film, and subjecting the coating to curing treatment to obtain a super hydrophobic coating.

2. The preparation method of super hydrophobic coating according to claim 1, wherein The step B specifically comprises: The sand and gravel particles are cleaned and then spread out to air dry; The air-dried sand and gravel particles are placed in an acid etching solution, and after being acid-etched for a predetermined time, they are dried to obtain etched sand and gravel particles.

3. The preparation method of super hydrophobic coating according to claim 2, characterized in that, The acid etching solution includes H2O, HF and HCl, and the volume ratio of H2O, HF and HCl is 30:4.5-10:

1.

4. The preparation method of super hydrophobic coating according to claim 2, characterized in that, The predetermined time is 8-12 hours.

5. The preparation method of super hydrophobic coating according to claim 1, characterized in that, The step C specifically comprises: placing the etched sandstone particles in a 1H, 1H, 2H, 2H-heptadecafluorodecyl trichlorosilane solution to perform surface modification treatment to obtain milli-nanostructured sandstone particles; The 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane solution is prepared from 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane and an organic solvent, and the organic solvent includes at least one of n-hexane, ethanol and dichloromethane.

6. The method for preparing a super hydrophobic coating according to claim 5, wherein The surface modification treatment time is 10 to 12 hours.

7. The method for preparing a super hydrophobic coating according to claim 5, wherein The mass ratio of the volume of the organic solvent to 1H,1H,2H,2H-heptadecafluorodecyltrichlorosilane is 30mL:0.5-1g.

8. The method for preparing a super hydrophobic coating according to claim 1, wherein In the step D, the adhesive is epoxy resin, silicone resin, acrylic resin or a two-component adhesive, and the thickness of the adhesive film is 1 to 3 mm.

9. The method for preparing a super hydrophobic coating according to claim 1, wherein In the step E, the curing time is 18 to 36 hours.

10. A super hydrophobic coating, characterized in that: The super hydrophobic coating is prepared by the preparation method of the super hydrophobic coating according to any one of claims 1 to 9; And / or, the super-hydrophobic coating includes a film and milli-nano structured gravel particles uniformly distributed on the surface of the film, and the milli-nano structured gravel particles include gravel particles with a diameter of millimeters and nanostructures combined on the surface of the gravel particles.

Citation Information

Patent Citations

  • Surface processing method of super-hydrophobic ice-covering-proof aluminum and steel with rough surface

    CN101705488A

  • Preparation method of super-hydrophobic coating layer on aluminum surface

    CN105521934A

  • High-performance super-hydrophobic metal surface and manufacturing method thereof

    CN110756414A

  • Preparation method of super-hydrophobic and oleophobic coating

    CN114773997A

  • Preparation method of micro-nano composite high-stability super-amphiphobic metal corrosion prevention and inhibition material

    CN117483212A